Chromatin Interaction Responds to Breast Muscle Development and Intramuscular Fat Deposition Between Chinese Indigenous Chicken and Fast-Growing Broiler - Tian, Weihua; Wang, Zhang; Wang, Dandan; Zhi, Yihao; Dong, Jiajia; Jiang, Ruirui; Han, Ruili; Li, Zhuanjian; Kang, Xiangtao; Li, Hong; Liu, Xiaojun (Frontiers in Cell and Developmental Biology, 2021)
Skeletal muscle development and intramuscular fat (IMF) content, which positively contribute to meat production and quality, are regulated by precisely orchestrated processes. However, changes in three-dimensional chromatin structure and interaction, a newly emerged mediator of gene expression, during the skeletal muscle development and IMF deposition have remained unclear. In the present study, we analyzed the differences in muscle development and IMF content between one-day-old commercial Arbor Acres broiler (AA) and Chinese indigenous Lushi blue-shelled-egg chicken (LS) and performed Hi-C analysis on their breast muscles. Our results indicated that significantly higher IMF content, however remarkably lower muscle fiber diameter was detected in breast muscle of LS chicken compared to that of AA broiler. The chromatin intra-interaction was prior to inter-interaction in both AA and LS chicken, and chromatin inter-interaction was heavily focused on the small and gene-rich chromosomes. For genomic compartmentalization, no significant difference in the number of B type compartments was found, but AA had more A type compartments versus LS. The A/B compartment switching of AA versus LS showed more A to B switching than B to A switching. There were no significant differences in the average sizes and distributions of topologically associating domains (TAD). Additionally, approximately 50% of TAD boundaries were overlapping. The reforming and disappearing events of TAD boundaries were identified between AA and LS chicken breast muscles. Among these, the HMGCR gene was located in the TAD-boundary regions in AA broilers, but in TAD-interior regions in LS chickens, and the IGF2BP3 gene was located in the AA-unique TAD boundaries. Both HMGCR and IGF2BP3 genes exhibited increased mRNA expression in one-day-old AA broiler breast muscles. It was demonstrated that the IGF2BP3 and HMGCR genes regulated by TAD boundary sliding were potential biomarkers for chicken breast muscle development and IMF deposition. Our data not only provide a valuable understanding of higher-order chromatin dynamics during muscle development and lipid accumulation but also reveal new insights into the regulatory mechanisms of muscle development and IMF deposition in chicken.